2008
DOI: 10.1111/j.1447-0756.2008.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammatory markers in normal pregnancy and preeclampsia

Abstract: Aim: Although previous investigators have demonstrated the presence of oxidative stress and inflammation in preeclampsia, none directly correlate both to preeclampsia. Methods: We determined in 35 preeclamptic and 35 normotensive pregnant women plasma levels of thiobarbituric acid reactive species, protein carbonyl, tumour necrosis factor-a (TNF-a), interleukin-1b (IL-1b), IL-6 and IL-10. Results: Plasma thiobarbituric acid reactive species and protein carbonyls were higher in preeclamptic patients. TNF-a and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 14 publications
5
52
0
5
Order By: Relevance
“…For individual cytokines, we observed increased TNF-a and IL-6 and reduced IL-10 in the combined pre-eclampsia cohort compared with matched normal pregnancy controls; these are consistent with other published reports. [40][41][42][43][44][45][46] The imbalance between inflammatory and anti-inflammatory cytokines probably contributes to endothelial dysfunction, 47 and is therefore linked with the pathogenesis of preeclampsia…”
Section: Discussionmentioning
confidence: 99%
“…For individual cytokines, we observed increased TNF-a and IL-6 and reduced IL-10 in the combined pre-eclampsia cohort compared with matched normal pregnancy controls; these are consistent with other published reports. [40][41][42][43][44][45][46] The imbalance between inflammatory and anti-inflammatory cytokines probably contributes to endothelial dysfunction, 47 and is therefore linked with the pathogenesis of preeclampsia…”
Section: Discussionmentioning
confidence: 99%
“…The increased oxidative stress may also contribute to endothelial dysfunction and the presence of increased proinflammatory cytokines such as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor (TNF) α, all of which have been linked to adverse pregnancy outcomes (17). Moreover, the studies have shown that chronic deprivation of sleeping can enhance immune response and level of inflammatory factors such as interleukin (IL-1), IL-2, IL-6, IL-10, INF-α and C-reactive protein (CRP) considerably (18)(19)(20)(21)(22). OSA with reduction of leptin level can lead to disorder in blood sugar control.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies showed nutrients may be involved in several important steps in the current proposed concepts of the pathogenesis of PE (31). The underlying mechanisms are complex and remain unclear (8)(9)(10). To date there has been controversial results in this issue.…”
Section: Discussionmentioning
confidence: 93%
“…Despite extensive studies and recent evidence to identify the pathophysiology of PE, the etiology of this disorder is questionable and requires further investigation (8). Disturbed placentation, endothelial dysfunction, oxidative stress and a low-grade systemic inflammatory condition are related to the diagnostic criteria for PE, leading to the clinical signs including hypertension, proteinuria and edema after the twentieth week of pregnancy (9,10).…”
Section: Introductionmentioning
confidence: 99%